Monitoring broiler breeder flocks for Mycoplasma gallisepticum Infection after vaccination with ts-11 - Bisschop, Shahn P.R. (University of Pretoria, 2013)
Dissertation (MMedVet (Altil.))--University of Pretoria, 2004.